Assessment the Nutritional Status by Anthropometric measurements for the students of secondary schools in Al- Hilla city - Hasab, Ali Husain; Husain, KahtanHadi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Nutritional status is indicator of person and community level well-being and safety where it is necessary to identify risk status while planning health promotion activities, nutritional diagnosis and disease prevention. In several ways linked to nutritional status, anthropometrics is used as markers of fitness, growth and development in childhood and adolescence. Objectives: this study conducted To assess the status of the nutrition for students in secondary schools using measurements of Anthropometric indices also To identify the relationship between anthropometric parameters and some affected variables including students Age ,Gender ,Family socio-economic level ,status of parents education, professional status of parents, size of house hold and rank of sibling. Methodology: Descriptive study conducted on the students of secondary schools of Al-Hilla city aged 12 to19 years for the period from 10th of February to the 15th of August of 2019. The selection of sample was conducted in two stages the first stage was choose 18 schools of secondary schools that found in Al-Hilla city then the second stage was selection the students were selected 421students from the schools of Hillacity . Results: the study results obtained that 73.3% of the boy students were have normal weight, 14.9% were overweight, 10.9% were obese and 1% of boys were under –weight, while in girls the percepts was: 69.4%, 14.6%, 12.3% and 10.9% normal weight , overweight, obesity and underweight respectively. also this study estimated that there is significance relationship between triceps skin fold thickness and the gender. Conclusions and recommendations: According to the body mass index the percent of girls who have overweight was 14.6% and obesity was 12.3% while in male the obesity percent was 10.9 % and overweight was 14.9%. so must Educate the students to emphasis on the quality of the eaten food not on quantity.